E?ects of Preloading with Isotonically Balanced Tetra Hydroxyethyl Starch Versus Preloading with Gelufusine On Blood Glucose Level in Diabetic Patients - Chandra, Amit Prakash (Academia Anesthesiologica International, 2020)
Background: The present study was conducted to study the effects of preloading with isotonically balanced tetra hydroxyethyl starch versus preloading with Gelufusine on blood glucose levels in diabetic patients. Subjects and Methods: 50 patients were diabetic categorized as study group (Group S) and 50 patients were nondiabetic categorized as a control group (Group C). Group C1 was non-diabetic patients who received gelofusine 10 ml/kg as preloading fluid 30 minutes prior to general anaesthesia, group C2 was non-diabetic patients who received 6% Hydroxyethyl starch 10 ml/kg as preloading fluid 30 minutes prior to general anaesthesia, group S1 was controlled diabetic patients who received gelofusine 10 ml/kg as preloading fluid 30 minutes prior to general anaesthesia and group S2 was controlled diabetic patients who received 6% Hydroxyethyl starch 10 ml/kg as preloading fluid 30 minutes prior to general anaesthesia. Results: There was no statistically significant difference in age, weight, height and the duration of surgery of patients between four groups (p>0.05). In the four groups of patients included in the study, female patients outnumbered the male patients but the difference was not statistically significant (p>0.05). There was no statistically significant difference in the baseline blood glucose values between all four groups. The blood glucose level in group C1 and S1 recorded a maximum decrease at 60 minutes. In group C2 and S2, there was the increase in blood glucose level at 60 minutes. Conclusion: Gelofusine fluid preloading produces a better outcome in diabetic patients as compared to preloading with hydroxyethyl starch fluid.